Gender Agency at the Intersection of State, Market and Family: Changes in Fertility and Maternal Labor Supply in Eight Countries - Lynn Prince Cooke (Luxembourg Income Study (LIS), 2001)
Current debates on the welfare state entail two intertwined questions. First, does a nation have sufficient active labor force participation to maintain the benefits for non-participants? Second, do social provisions exacerbate or attenuate class, ethnic and other distinctions within society? As predominantly structural or institutional debates, these discussions tend to exclude the impact social provisions have on facilitating individual agency among members of social groups. Yet the institutions of state, market and family interact to shape a gender order which specifies the types of social or civil claims that can be made by individuals. The gender order yields the societal boundaries within which agency can be exercised. This paper will present comparative evidence of how the package of social provisions in combination with market factors manifests in women's agency regarding family choices in eight countries. This, in turn, provides material evidence of whether the institutionally-framed gender order encourages gender difference or equity in terms of paid and unpaid work.
Keywords: 330; Weibliche Arbeitskräfte; Fertilität; Luxemburg; Finnland; USA; Kanada; Großbritannien; Deutschland; Australien; Schweden